Analisis Penentuan Sektor Unggulan Perekonomian Di Kawasan Minapolitan Provinsi Jawa Timur - Siti Nurafiah; Endah Kurnia Lestari; Siti Komariyah (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2020)
Fisheries are all activities that related to the management, utilization of fish resources and their environment, including production, processing and marketing activities that carried out in a fisheries business. The purpose of this study was to analyze the growth and potential of the district fisheries sub-sector in the Minapolitan Region of East Java Province. The analytical method that used in this study are Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Shift Share Esteban Marquillas (SS-EM). The analysis of the Location Quotient (LQ) showed that from 2012 to 2016 district that had the highest average LQ was Lamongan District ( LQ 7.81). The analysis of the Dynamic Location Quotient (DLQ) showed that the district with the highest potential/ competitiveness in the future is Blitar (DLQ 1.40).